+0  
 
0
292
1
avatar

Given that g is the inverse function of f, and f(3)=4, and f'(3)=5, then g'(4) = 

 

  • -1/5
  • 3/5
  • 1/5
  • 1/4
Guest May 24, 2017
 #1
avatar+92856 
+1

 

The derivative of the inverse function is given by :

 

g'(x)  =   1 / [ f ' (g (x) ) ]

 

Note that  ( 3, 4)  is on  " f " so   (4, 3)  is on   " g "    so.....g (4)  = 3

 

So

 

g ' ( 4)  =  1 / [ f ' ( g (4) ) ]  =   1 / [ f ' (3) ]  =   1 / [ 5 ]   =   1 / 5 

 

 

 

cool cool cool

CPhill  May 24, 2017
edited by CPhill  May 24, 2017

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.